Analisis Kinerja Bisnis Parfum Heaven In Bottle Di Kota Palembang - Wandira, Riri Ayu; Fakhirah, JIhan; Fitriansyah, Zakky; Kasih, Yulizar (Universitas Multi Data Palembang, 2024)
Heaven In Bottle perfume is a business engaged in cosmetics. A perfume is a mixture of essential oils and aroma compounds, fixatives and solvents used to give a fragrant scent. This business offers two types of choices, namely men's and women's perfumes with 5 variants each with a size of 35ml. This business is located on Jl. Makam Sabokingking GHB Block A No. 11, Palembang City. Promotions that will be carried out using social media such as influencers and celebrities. Based on the aspect of business performance, Heaven In Bottle perfume is declared capable of competing and developing in the future.